2011
DOI: 10.1371/journal.pone.0018406
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclophilin-Binding Agent Sanglifehrin A Is a Dendritic Cell Chemokine and Migration Inhibitor

Abstract: Sanglifehrin A (SFA) is a cyclophilin-binding immunosuppressant but the immunobiology of action is poorly understood. We and others have reported that SFA inhibits IL-12 production and antigen uptake in dendritic cells (DC) and exhibits lower activity against lymphocytes. Here we show that SFA suppresses DC chemokine production and migration. Gene expression analysis and subsequent protein level confirmation revealed that SFA suppressed CCL5, CCL17, CCL19, CXCL9 and CXCL10 expression in human monocyte-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…SfA ( 40 ) binds in the active site of cyclophilin A, but immunosuppressive activity is not caused by calcineurin binding (Table ). Additionally, there is no inhibition of mTOR or of the purine/pyrimidine de novo synthesis . The mechanism of immunosuppression seems to be connected to dendritic cell (DC) chemokine and migration inhibition but remains to be fully elucidated. , Degradation studies on SfA ( 40 ) revealed that removal of the C24 polyketide side chain (corresponding to R 1 in Table ) eliminated the immunosuppressive properties of the molecule while maintaining the nanomolar binding affinity to hCypA, -B, and -C. ,, One of these nonimmunosuppressive sanglifehrins, AAE931 ( 41 , Table ), showed potent anti-HCV activity in the replicon assay (IC 50 = 130 nM) …”
Section: Potential To Develop Inhibitors Of Bacterial Cyclophilinsmentioning
confidence: 99%
See 2 more Smart Citations
“…SfA ( 40 ) binds in the active site of cyclophilin A, but immunosuppressive activity is not caused by calcineurin binding (Table ). Additionally, there is no inhibition of mTOR or of the purine/pyrimidine de novo synthesis . The mechanism of immunosuppression seems to be connected to dendritic cell (DC) chemokine and migration inhibition but remains to be fully elucidated. , Degradation studies on SfA ( 40 ) revealed that removal of the C24 polyketide side chain (corresponding to R 1 in Table ) eliminated the immunosuppressive properties of the molecule while maintaining the nanomolar binding affinity to hCypA, -B, and -C. ,, One of these nonimmunosuppressive sanglifehrins, AAE931 ( 41 , Table ), showed potent anti-HCV activity in the replicon assay (IC 50 = 130 nM) …”
Section: Potential To Develop Inhibitors Of Bacterial Cyclophilinsmentioning
confidence: 99%
“…123 SfA (40) binds in the active site of cyclophilin A, 137 but immunosuppressive activity is not caused by calcineurin binding (Table 6). 138 Additionally, there is no inhibition of mTOR or of the purine/pyrimidine de novo synthesis. 139 The mechanism of immunosuppression seems to be connected to dendritic cell (DC) chemokine and migration inhibition but remains to be fully elucidated.…”
Section: ■ Potential To Develop Inhibitors Of Bacterial Cyclophilinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immecke et al recently claimed that SfA-mediated suppression of chemokine and CD38 receptor expression in monocyte-derived dendritic cells (moDC) is unique and independent of CyPA [129]. However, they found more of a reduction of chemokines CCL5, CCL17, and CCL19 when moDC were treated with a combination of SfA and CsA, than when treated with SfA or CsA alone.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Combined pharmacological approaches are also a feasible possibility. In this regard, treatments with CsA, a cycophilin‐interacting drug, associated to other natural compounds such as sanglifehrin efficiently suppresses chemokine signalling and cell migration . It has been proposed that the use of rapamycin along with metrothrexate and tacrolimus in patients with lymphoma is associated with a significantly decreased risk of disease progression, although a recent clinical trial performed in children with acute lymphatic leukemia also showed increased toxicity and disapproved the therapeutic combination of these drugs.…”
Section: Future Therapies With Selective Small Moleculesmentioning
confidence: 99%